Status and consensus: Heterogeneity in audience evaluations of female‐ versus male‐lead films - Stroube, Bryan K.; Waguespack, David M. (Strategic Management Journal, 2024)
Abstract Research Summary Extant research finds that status characteristics such as gender are frequently related to average quality evaluations by external audiences, but little is known about whether such characteristics are also related to consensus in quality evaluations. We examine 383 million film ratings by consumers to document that female‐lead movies elicit less consensus in quality evaluations than male‐lead movies. In split‐sample analyses, we find that male raters are more negative than female raters about female‐lead titles, and that the two audiences differ on dispersion and skew. A subsequent experiment helps distinguish between various mechanisms that might be driving these results, including actor sorting, audience sorting, and treatment effects on audience quality perceptions. Finally, we find that independent studios yield greater box office revenue from female‐lead movies. Managerial Summary Consumers often lack consensus about product quality. Does product gender‐typing influence perceived quality consensus? We examine this question in the film industry, where 28.5% of films from 1992 to 2018 had a female actor in the lead role. Using 383 million consumer ratings from a popular website, we find less consensus in ratings of female‐lead films compared to male‐lead films. Some of this effect stems from male audiences who, compared to female audiences, rate female‐lead films lower than male‐lead films and disagree more on their quality. We use an experiment with fictional AI‐generated movie plots and random lead‐actor gender to better understand what drives this effect. Finally, we find independent studios have higher box office revenue from female‐lead films.